Fears and Misperceptions of the Ebola Response System during the 2014-2015 Outbreak in Sierra Leone. - Thespina Yamanis; Elisabeth Nolan; Susan Shepler (Public Library of Science (PLoS), 2016)
BACKGROUND:Future infectious disease epidemics are likely to disproportionately affect countries with weak health systems, exacerbating global vulnerability. To decrease the severity of epidemics in these settings, lessons can be drawn from the Ebola outbreak in West Africa. There is a dearth of literature on public perceptions of the public health response system that required citizens to report and treat Ebola cases. Epidemiological reports suggested that there were delays in diagnosis and treatment. The purpose of our study was to explore the barriers preventing Sierra Leoneans from trusting and using the Ebola response system during the height of the outbreak. METHODS:Using an experienced ethnographer, we conducted 30 semi-structured in-depth interviews in public spaces in Ebola-affected areas. Participants were at least age 18, spoke Krio, and reported no contact in the recent 21 days with an Ebola-infected person. We used inductive coding and noted emergent themes. FINDINGS:Most participants feared that calling the national hotline for someone they believed had Ebola would result in that person's death. Many stated that if they developed a fever they would assume it was not Ebola and self-medicate. Some thought the chlorine sprayed by ambulance workers was toxic. Although most knew there was a laboratory test for Ebola, some erroneously assumed the ubiquitous thermometers were the test and most did not understand the need to re-test in the presence of Ebola symptoms. CONCLUSION:Fears and misperceptions, related to lack of trust in the response system, may have delayed care-seeking during the Ebola outbreak in Sierra Leone. Protocols for future outbreak responses should incorporate dynamic, qualitative research to understand and address people's perceptions. Strategies that enhance trust in the response system, such as community mobilization, may be particularly effective.